Comparative field evaluation of mechanized and manual cassava production operations: the case of cassava farmers in Ogun state of Nigeria - Abass, A.; Okechukwu, R.; Gworgwor, N.; Amaza, P.; Awoyale, W. (2021)
In 2015, mechanized technologies for planting and harvesting cassava were introduced to farmers involved in the Cassava Value Chain (CVC) in Ogun State of Nigeria for testing. This study comparatively analysed the profitability of cassava production under mechanized and manual operations. Partial budgeting was used to compare costs and benefits of the new innovations with manual process. The comparison was based on data obtained from farmers involved in an effort to enhance the competitiveness of high quality cassava flour (HQCF). The results revealed that yields from harvested fresh cassava roots on mechanically planted cassava farm plots increased by 38% over the manually planted cassava farm plots. The main gain associated with the mechanized process was the relatively lower costs associated with planting and harvesting operations, which were cheaper over the manual operations by 55% and 59%, respectively. The mechanically and manually planted cassava farm plots have a gross margin of $491/ha and $296/ha, respectively. Comparison of these levels of profitability showed that the mechanized operations were relatively more profitable and exceeded the manual farm operations by 83%. Thus, the study concludes that the mechanization of cassava planting and harvesting, combined with high-yielding variety and complementary agronomic practices, can lead to higher competitiveness and economic break-through for cassava farmers in Africa. Therefore, we recommend increased efforts to scale-up mechanized cassava production operations, including building the capacity of cassava farmers with regards to improved production technologies and crop management practices.